Estudo da interação Liriomyza sativae – meloeiro por meio de metabolômica, utilizando RMN - Ferreira, Italo Juan Lima (2024)
Melon (Cucumis melo L.) has socioeconomic importance in the Brazilian semi-arid region, which accounts for more than 95% of this agribusiness. Modern cultivation technologies combined with edaphoclimatic conditions and the international window favorable to Brazilian exports result in intense and consecutive plantings, which favors phytosanitary problems, especially the leafminer fly (Liriomyza sativae Blanchard), the main cultivation problem and responsible for 15% of production costs of production. In this scenario, Embrapa has been concentrating efforts on identifying sources of resistance and on strategies for introducing resistance into lineages and elite hybrids through conventional and biotechnological strategies such as characterization of metabolites in melon genotypes resistant and susceptible to the leafminer fly. Thus, the objective of this study was to associate the profile of primary metabolites with the resistance reaction due to antibiosis and/or susceptibility to L. sativae due to through metabolomic analysis of leaves from melon genotypes. To this end, five melon genotypes (resistant and susceptible lines of BAGMEL 56 and CNPH 00-915 and the resistant commercial hybrid Tântalo) were subjected to controlled infestation with leafminer flies and leaves were collected before infestation (time 0); three days after infestation in cages with fly adults (time 1.a); and three days after infestation in cages without fly adults (time 1.b). The collected leaves were immediately weighed, frozen in liquid N 2, stored in a freezer at -80 ºC and subjected to metabolomic analysis using Nuclear Magnetic Resonance, at LMQPN. The following metabolic groups were identified in the analyzed genotypes: organic acids, amino acids, carbohydrates and other compounds. With highlights for the metabolites: formic acid, threonine and valine which were not identified in all genotypes. The main primary metabolite associated with resistance was methanol and with susceptibility was acetic acid.